An Analysis of miscommunication in the Kansai dialect among Indonesian internship students - Aqeela Putri Aisyah; Setiyani Wardhaningtyas (Japanese Research on Linguistics, Literature, and Culture, 2026)
This study aims to identify and analyze Kansai dialect miscommunication experienced by 2021 Japanese Language Education students at Semarang State University during their internship program as caddies at Ise Country Club, Japan. The study uses a qualitative descriptive approach with participatory observation and in-depth interviews. Data analysis was conducted through reduction, presentation, and conclusion drawing, with classification into lexical and pragmatic miscommunication. Lexical miscommunication arose when students interpreted Kansai dialect vocabulary literally based on standard Japanese, resulting in responses that did not match the speaker's intention. Pragmatic miscommunication occurred due to students' limitations in understanding implicit meaning, speech functions, and politeness strategies that affect the smoothness of interaction. These findings emphasize the importance of mastering local dialect vocabulary as well as understanding social context and pragmatic strategies. The practical implications are the need for training before internships and further studies on interactions with other dialect variations in Japan.